A Brief History of the Chuck Wagon - Josh Hoy (Symphony in the Flint Hills, 2010)
I am a 5th generation Flint Hills rancher. My grandfather, Kenneth Hoy, drove cattle from Texas to Kansas as a teenager, and my great-uncle, Marshal Hoy, was as famous for his sourdough biscuits as he was for the horses he raised. So it is with pride and an acute awareness of my heritage that I inform you that we Hoys are kin to Charles Goodnight, the trail-blazing rancher and inventor of the chuck wagon. It is a distant kinship, but we claim it with pride. My great-great-uncle, Frank Goodnight, was Charley’s great-nephew. The chuck wagon was an essential piece of equipment for cowboys and ranchers during the trail-driving years and the era of open range ranching.
Keywords: chuck wagon; heritage; trail; travel; cowboy; rancher; ranch; farm; cattle; cow; trail-driving; cattle-drive; range; food; mobile; kitchen; cook; Charley Goodnight; Charles Goodnight